2020
DOI: 10.3390/ijerph17092985
|View full text |Cite
|
Sign up to set email alerts
|

Mother–Infant Co-Sleeping and Maternally Reported Infant Breathing Distress in the UK Millennium Cohort

Abstract: Mother–infant co-sleeping or bed sharing is discouraged by health organisations due to evidence that it is associated with unexplained sudden infant death. On the other hand, there is evidence that it should theoretically be beneficial for infants. One line of this evidence concerns breathing regulation, which at night is influenced by the rocking movement of the mother’s chest as she breathes. Here, the hypothesis that mother–infant co-sleeping will be associated with a lower probability of infant breathing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…A typical example of those efforts is to avoid cosleeping on sofa or couch which increases the likelihood of child’s breathing regulation. 52 The enumerators employed for this survey rarely observed sofa and couch during household visits. Thus, the risks of SUDI to be derived from mother–infant cosleeping in the two districts should be quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…A typical example of those efforts is to avoid cosleeping on sofa or couch which increases the likelihood of child’s breathing regulation. 52 The enumerators employed for this survey rarely observed sofa and couch during household visits. Thus, the risks of SUDI to be derived from mother–infant cosleeping in the two districts should be quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…For example, young children can maintain homeostasis of vital functions, such as heart rate and respiration, but the regulatory role of parental care was shown through experiments comparing infants alone v. engaged in parental contact via somatosensory (temperature, touch), olfactory (caregiver odor), visual (face), and auditory (voice) stimulation ( Kommers et al, 2019 ; Suga et al, 2019 ; Buhler-Wassmann and Hibel, 2021 ; Ionio et al, 2021 ). This regulation is also seen in the infant’s co-sleep with the parent, producing improved sleep compared to when the infants sleep alone ( Mosko et al, 1997 ; Richard and Mosko, 2004 ; Waynforth, 2020 ; Yoshida and Funato, 2021 ).…”
Section: Introductionmentioning
confidence: 92%
“…The other two papers analyzed ad hoc nationwide prospective birth cohorts set in Japan (Japan Environment and Children’s Study [ 22 ]) and the UK (UK Millennium Cohort Study [ 23 ]). Both the topics covered in these studies (co-sleeping associated with less breathing difficulties and child development in relation to pet ownership at an early age) could not be assessed through retrospective real word data.…”
mentioning
confidence: 99%
“…The recorded information is related to pregnant women who compiled the self-administered questionnaire between January 2011 and March 2014. Waynforth et al used data drawn from the UK Millennium Cohort Study which recorded self-reported information from the mothers of 18,552 infants born from September 2000 to August 2001 in the UK [ 23 ].…”
mentioning
confidence: 99%